Group Formation in a Public Good Experiment. On The Dynamics of Social Ties Structures - Frans van Winden (Center for Economic Studies and ifo Institute (CESifo), 2000)
Economic behavior often takes place in groups of small numbers of people interacting with each other (like work teams, neighborhoods, social networks, etc.). Characteristic of such interaction is the development of (affective) interpersonal relationships, or social ties. According to sociologists, the embeddedness of economic behavior in networks of social ties has a profound impact on economic performance. Although, in economics, there is a growing awareness of the significance of social factors, the study of social dynamics is still in its infancy. In this paper we investigate experimentally the development of social ties structures, and thereby the formation of informal groups, through economic interaction in a public good environment. It turns out that complicated dynamics arise from individual differences in social value orientation and (affective) response patterns. Our findings point at the importance of leadership in controlling and channeling emotions and sentiments to build effective groups, like teams or communities. This leads to a different perspective on management than the one provided by standard agency theory.
Keywords: 330